2019
DOI: 10.1596/1813-9450-8865
|View full text |Cite
|
Sign up to set email alerts
|

Tackling the Global Profitarchy: Gender and the Choice of Business Sector

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…In terms of practical implications, we help to dispel the misconception that women receive less funding because they start businesses in female-dominated industries that require less capital than male-dominated ones (54,55). Although female-led ventures were associated with less funding than comparable male-led ventures across both of our studies, we found that female founders raised significantly more (not less) funding when catering to female-dominated industries considered a fit for them.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of practical implications, we help to dispel the misconception that women receive less funding because they start businesses in female-dominated industries that require less capital than male-dominated ones (54,55). Although female-led ventures were associated with less funding than comparable male-led ventures across both of our studies, we found that female founders raised significantly more (not less) funding when catering to female-dominated industries considered a fit for them.…”
Section: Discussionmentioning
confidence: 99%
“…This section draws on the Future of Business Survey, a collaboration between Facebook, the OECD and the World Bank to provide data on online firms that have an active Facebook business page. 26 The Future of Business Survey should not be considered representative of all business owners, but rather micro, small and medium-sized firms with an online presence on Facebook (Goldstein et al, 2019).…”
Section: Women Entrepreneurs and Business Ownersmentioning
confidence: 99%
“…Women-led firms tend to be younger than the average. In the United States, the average age of womenled firms is 43 months, compared with the average of 52 months for those not led by women in 2018 (Biz2Credit, 2019;Goldstein et al, 2019) Among firms with a Facebook presence, firms owned and led by men are overwhelmingly represented among firms that have existed for over ten years (Facebook-OECD-World Bank Future of Business survey, June 2019).…”
Section: Annex C Characteristics Of Women-owned Firms and The Barriementioning
confidence: 99%
“…Men's and women's jobs differ across sectors, occupations, types of jobs, and firms as multiple factors lead to gender segregation with important implications for gender gaps in earnings (Goldstein et al, 2019). The World Development Report on gender (World Bank, 2012) posited that these differences stemmed from three main factors: (i) unequal distribution of time use and care responsibilities between men and women and between households and public/private service provision; (ii) unequal access to and control over productive assets (particularly land, credit, insurance and savings but also key skills); and (iii) market and institutional failures (access to information and networks, legal and fiscal impediments, restrictive social norms).…”
Section: Investments In Adult Womenmentioning
confidence: 99%